Pengaruh Lingkungan Kerja dan Semangat Kerja Terhadap Produktivitas Kerja Karyawan Produksi PD. Galunggung - Sugestianita, Mitra; Askolani; Barlian, Barin (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This research aims to determine the simultaneous or partial influence of Work Environment and Work Spirit variables on Work Productivity. The population used in this study were 57 PD employees. Galunggung Putra. The method used in this research is descriptive research with a quantitative approach. Sample selection uses saturated samples. The sample used is the entire population, namely 57 PD employees Galunggung Putra. Sources of data in this study are secondary data and primary data. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the research results, it is concluded that the Work Environment and Work Morale simultaneously have a significant effect on Work Productivity. The work environment partially has a significant effect on work productivity. Morale partially has a significant effect on work productivity.